Evaluating Ground Grain Sorghum as an Alternative to Dry-Rolled Corn in Finishing Cattle Diets - Harleigh Johnson; Sarah A. Sexton-Bowser; Jaymelynn K. Farney; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The aim of this study was to evaluate ground grain sorghum as an alternative to dry-rolled corn. Study Description: Beef steers (n = 300; 764 lb initial body weight) in 30 feedlot pens (10 animals/pen; 15 replicates) were fed finishing diets containing ground sorghum or dry-rolled corn for 182 days. Diets were balanced to contain similar crude protein and starch and fed once daily. Average daily gain, dry matter intake, feed efficiency, carcass traits, and digestibility of diet components were determined. The Bottom Line: The energy value of ground sorghum grain was approximately 94% that of dry-rolled corn. Future efforts should focus on the development of superior sorghum hybrids and processing methods that enhance nutritional value of sorghum.
Keywords: sorghum; feedlot; beef